Efforts To Improve Reading Ability Through The Media Of Picture Card Games In Class 1st Students Of State Elementary School 004 Kepenuhan - Nursyaadah Nursyaadah (STKIP Rokania Pasir Pangaraian, 2023)
This research was motivated by the low initial reading ability of grade 1 students at SD Negeri 004 Kepenuhan. One of the reasons is that teachers have not used the right media in learning. To overcome this problem, it is necessary to carry out classroom action research to improve the initial reading skills of grade 1 students at SD Negeri 004 Kepenuhan using picture card games as media. This research is Classroom Action Research (PTK) carried out in 2 cycles with 3 meetings per cycle with a total of 31 students. In pre-action, the percentage of student completion only reached 23%, after the action was implemented in cycle I, the percentage of student completion increased to 55%, in cycle II it increased to 77% so the researcher did not continue to cycle III